Why Words Are Hard for Adults With Developmental Language Impairments. - McGregor, Karla K.; Licandro, Ulla; Arenas, Richard; Eden, Nichole; Stiles, Derek; Bean, Allison; Walker, Elizabeth (Journal of Speech, Language & Hearing Research, 2013)
Purpose: To determine whether word learning problems associated with developmental language impairment (LI) reflect deficits in encoding or subsequent remembering of forms and meanings. Method: Sixty-nine 18- to 25-year-olds with LI or without (the normal development [ND] group) took tests to measure learning of 16 word forms and meanings immediately after training (encoding) and 12 hr, 24 hr, and 1 week later (remembering). Half of the participants trained in the morning, and half trained in the evening. Results: At immediate posttest, participants with LI performed more poorly on form and meaning than those with ND. Poor performance was more likely among those with more severe LI. The LI-ND gap for word form recall widened over 1 week. In contrast, the LI and ND groups demonstrated no difference in remembering word meanings over the week. In both groups, participants who trained in the evening, and therefore slept shortly after training, demonstrated greater gains in meaning recall than those who trained in the morning. Conclusions: Some adults with LI have encoding deficits that limit the addition of word forms and meanings to the lexicon. Similarities and differences in patterns of remembering in the LI and ND groups motivate the hypothesis that consolidation of declarative memory is a strength for adults with LI.